Reflection and transmission of quasi-P waves through an orthotropic layer sandwiched between two half-spaces - Tung, Do Xuan; Kieu, Nguyen Thi; Thang, Luong The (Vietnam Journal of Mechanics, 2018)
In this paper, the reflection and transmission of a qP wave through an orthotropic elastic layer sandwiched between two orthotropic elastic half-spaces is investigated. The main aim is to derive the expressions in closed-form of the reflection and transmission coefficients. These expressions have been obtained by using the transfer matrix for an orthotropic layer. Based on the obtained expressions, some numerical examples are carried out to examine the dependence of the reflection and transmission coefficients on the incident angle, the wave frequency and the ratio of mass densities.